Factors influencing the behavior in recycling of e-waste using integrated TPB and NAM model - Lidwin Kenneth Michael; Sumukh S. Hungund; Sriram K. V. (Cogent Business & Management, 2024)
The rapid advancement of technology across multiple sectors including education, the workplace, manufacturing, and household appliances, has resulted in a notable increase in the prevalence of electronic gadgets. Therefore, these devices, also known as e-waste, are discarded once they have reached the end of their useful life. The focus of the study is to identify and examine the factors that influence students' intentions toward the disposal of e-waste. The study adopts a quantitative approach with a cross-section study design to collect data from 415 participants selected through a purposive sampling method. The data was collected through an online survey. The study found that factors such as Environmental Knowledge, Public Awareness, Publicity, Convenience, Infrastructure, Willingness to Pay (WTP), Data security, and Personal norms positively influence students' intentions toward e-waste disposal behavior. This paper delineates the fundamental characteristics of e-waste management strategies that prioritize customer needs and presents a comprehensive framework for India. Policymakers must prioritize increasing customers' willingness to pay (WTP), offering support in advertising efforts, and ensuring robust data protection. Additionally, supporting education on environmental awareness is of utmost importance.
Keywords: 650; E-waste; theory of planned behaviour; recycling intention; willingness to pay; awareness